Toward a General Theory of Client Acceptance and Continuance Decisions - Drira, Mohamed (Journal of Comparative International Management)

(untitled) (Management Futures, 2013)
This study investigates the theoretical perspectives used in the extant auditing literature on client acceptance and continuance decisions. First, the different client acceptance and continuance decisions are presented. Second, the paper identifies and discusses the single-client approach and introduces “the auditor-client relationship life cycle” as an integrative framework for this perspective commonly used in academia. Third, the audit firm portfolio management perspective is examined. Finally, the apparent incommensurability of the single-client and the clients-portfolio approaches is discussed and the foundation for a general theory of the client acceptance and continuance decisions is developed.